Over all sets of real numbers ( x , y ) such that x 2 + y 2 = 1 , find the maximum value of F ( x , y ) = ( 3 x + 4 y ) 2 + ( 8 x + 6 y ) 2
to 2 decimal places
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Nice approach.(+1.
Consider the linear transformation A = ( 3 8 4 6 ) . By performing Singular Value Decomposition of this matrix, we find that the maximum singular value of the matrix A is 1 1 . 1 0 9 1 . Thus the maximum value of F ( x , y ) is simply the Rayleigh quotient of A T A , which is given by the square of the maximum singular value of A , i.e., 1 1 . 1 0 9 1 2 ≈ 1 2 3 . 4 1 .
We substitute x=sinß to get y=cosß from 1st relation. Now we write see second equation in form of sin2ß and cos 2ß and apply Cauchy Schwartz to get the answer
did the same way!
exactly what i did
here is a tricky method first we take x=0,y=1 then F(x,y)=16+36=52 second we take x=1,y=0 then F(x,y)=9+64=73 after that 52+73=125........got it
This solution is incorrect. There is no justification, nor is it correct, that max F ( x , y ) = F ( 0 , 1 ) + F ( 1 , 0 ) .
Why did u added the two values ???? That will give value of 2f(x,y)...
The elegant solution is :: as give x^{2} +y^{2} = 1 ..we can assume x=sin(a) and y=cos(a)..so max value of 3sin(a) + 4cos(a) = 5. and max value of 8sin(a) + 6cos(a) =10. Hence max value of f(x,y)=5^2 + 10^2 = 125.
Log in to reply
This is not justified as the two expressions attain maximum values at different values of a , namely a = 2 tan − 1 3 1 and a = 2 tan − 1 2 1 .
The correct approach would be to maximize 2 2 1 ( cos 2 a − sin 2 a ) + 1 2 0 sin a cos a + 2 1 2 5 = 2 1 ( 1 2 0 sin 2 a + 2 1 cos 2 a + 1 2 5 )
Hence, the maximum value of the expression would be max { F ( x , y ) } = 2 1 2 0 2 + 2 1 2 + 1 2 5 = 2 3 1 6 4 9 + 1 2 5 ≈ 1 2 3 . 4 1 1 8
So the answer provided is wrong.
Log in to reply
I too have done the same thing and got the same answer
first i find 123.412 but that was wrong so i take a tricky formula. it is just tricky not real.
L e t F ( x , y ) = ( 3 x + 4 y ) 2 + 4 ∗ ( 4 x + 3 y ) 2 L e t F ( m , n ) b e t h e p o i n t w h e r e F i s m a x i m u m , w i t h c o n d i t i o n t h a t i t i s a l s o o n x 2 + y 2 = 1 . ∴ t h e y h a v e c o m m o n t a n g e n t a t ( m , n ) . ⟹ d x d y m , n f r o m F ( x , y ) = 0 a n d x 2 + y 2 = 1 , a r e e q u a l . 2 x + 2 y d x d y = 0 . ⟹ d x d y = − y x . A n d d x d F = 2 ( 3 x + 4 y ) ∗ ( 3 + 4 d x d y ) + 8 ∗ ( 4 x + 3 y ) ∗ ( 4 + 3 d x d y ) = 0 . B u t d x d y = − y x , s u b s t i t u t i n g d x d y b y − y x , a n d m u l t i p l y i n g b y 2 y , d x d F = ( 3 x + 4 y ) ∗ ( 3 y − 4 x ) + 4 ∗ ( 4 x + 3 y ) ∗ ( 4 y − 3 x ) = 0 . ∴ − 1 2 x 2 − 7 x y + 1 2 y 2 − 4 8 x 2 + 2 8 x y + 4 8 y 2 = − 6 0 x 2 + 2 1 x y + 6 0 y 2 = 0 . ⟹ 2 0 ( x y ) 2 + 7 ( x y ) − 2 0 = 0 S o l v i n g q u a d r a t i c i n x y , x y = 0 . 8 4 0 1 9 7 . . . . . . . . . . . . . ( A ) ∴ x 2 y 2 = 1 0 . 7 0 5 9 3 1 . ⟹ x 2 + y 2 y 2 = 1 y 2 = 1 . 7 0 5 9 3 1 0 . 7 0 5 9 3 1 . ∴ y = 1 . 7 0 5 9 3 1 0 . 7 0 5 9 3 1 = 0 . 6 4 3 2 8 . ∴ b y ( A ) x = 0 . 8 4 0 1 9 7 0 . 6 4 3 2 8 = 0 . 7 6 5 6 3 . S o ( m , n ) = ( 0 . 7 6 5 6 3 , 0 . 6 4 3 2 8 ) . ∴ F ( m , n ) = 1 2 3 . 4 3 7 .
L e t F ( x , y ) = ( 3 x + 4 y ) 2 + 4 ∗ ( 4 x + 3 y ) 2 L e t F ( m , n ) b e t h e p o i n t w h e r e F i s m a x i m u m , w i t h c o n d i t i o n t h a t i t i s a l s o o n x 2 + y 2 = 1 . ∴ t h e y h a v e c o m m o n t a n g e n t a t ( m , n ) . ⟹ d x d y m , n f r o m F ( x , y ) = 0 a n d x 2 + y 2 = 1 , a r e e q u a l . 2 x + 2 y d x d y = 0 . ⟹ d x d y = − y x . A n d d x d F = 2 ( 3 x + 4 y ) ∗ ( 3 + 4 d x d y ) + 8 ∗ ( 4 x + 3 y ) ∗ ( 4 + 3 d x d y ) = 0 . B u t d x d y = − y x , s u b s t i t u t i n g d x d y b y − y x , a n d m u l t i p l y i n g b y 2 y , d x d F = ( 3 x + 4 y ) ∗ ( 3 y − 4 x ) + 4 ∗ ( 4 x + 3 y ) ∗ ( 4 y − 3 x ) = 0 . ∴ − 1 2 x 2 − 7 x y + 1 2 y 2 − 4 8 x 2 + 2 8 x y + 4 8 y 2 = − 6 0 x 2 + 2 1 x y + 6 0 y 2 = 0 . ⟹ 2 0 ( x y ) 2 + 7 ( x y ) − 2 0 = 0 S o l v i n g q u a d r a t i c i n x y , x y = 0 . 8 4 0 1 9 7 . . . . . . . . . . . . . ( A ) ∴ x 2 y 2 = 1 0 . 7 0 5 9 3 1 . ⟹ x 2 + y 2 y 2 = 1 y 2 = 1 . 7 0 5 9 3 1 0 . 7 0 5 9 3 1 . ∴ y = 1 . 7 0 5 9 3 1 0 . 7 0 5 9 3 1 = 0 . 6 4 3 2 8 . ∴ b y ( A ) x = 0 . 8 4 0 1 9 7 0 . 6 4 3 2 8 = 0 . 7 6 5 6 3 . S o ( m , n ) = ( 0 . 7 6 5 6 3 , 0 . 6 4 3 2 8 ) . ∴ F ( m , n ) = 1 2 3 . 4 3 7 .
Problem Loading...
Note Loading...
Set Loading...
Since x 2 + y 2 = 1 , we can let x = cos θ and y = sin θ . Therefore, we have:
F ( x , y ) = ( 3 x + 4 y ) 2 + ( 8 x + 6 y ) 2 = 7 3 x 2 + 1 2 0 x y + 5 2 y 2 As x 2 + y 2 = 1 = 2 1 x 2 + 1 2 0 x y + 5 2 = 2 1 cos 2 θ + 1 2 0 cos θ sin θ + 5 2 = 2 2 1 ( cos ( 2 θ ) + 1 ) + 6 0 sin ( 2 θ ) + 5 2 = 1 0 . 5 cos ( 2 θ ) + 6 0 sin ( 2 θ ) + 6 2 . 5 = 1 0 . 5 2 + 6 0 2 sin ( 2 θ + ϕ ) + 6 2 . 5 where ϕ = tan − 1 6 0 1 0 . 5
Since maximum of sin ( 2 θ + ϕ ) = 1 , then we have:
F ( x , y ) m a x = 1 0 . 5 2 + 6 0 2 + 6 2 . 5 = 6 0 . 9 1 1 8 2 1 5 1 + 6 2 . 5 ≈ 1 2 3 . 4 1